PERDAGANGAN SKINCARE “KW” DI PASAR TRADISIONAL PONTIANAK PERSPEKTIF KOMISI FATWA MAJELIS ULAMA INDONESIA NOMOR 1 TAHUN 2003 TENTANG HAK CIPTA - Noriraya Noriraya; Sukardi Sukardi; Abu Bakar (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2022)
This research is prompted by the widespread of sale particularly skincare in the counterfeiting of goods or